The The Role of Scaffolding in Optimizing Problem-Based Learning to Develop Students' Critical Thinking Skills - Nasha Aqilatuz Zahroh; Ali Shodikin (Jurnal Pedagogi dan Pembelajaran, 2025)
In the 2015 TIMSS, Indonesian students scored 397, ranking 44th out of 49 countries. This data suggests that Indonesian students consistently lack critical thinking skills in mathematics. The purpose of this study was to investigate the role of scaffolding within a Problem-Based Learning (PBL) framework in enhancing the critical thinking skills of junior high school students. This study employed a quantitative approach with a quasi-experimental design, which involved one experimental group. For this study, a random sample of 27 eighth-grade students was selected. Data were collected using a critical thinking test evaluated through an essay test created based on criteria established by Facione. Data analysis was carried out descriptively and inferentially. The data normality test, using the Shapiro Wilk test, showed that most of the data were not normally distributed; therefore, the inferential analysis was continued with the nonparametric Wilcoxon Signed Ranks Test. Data processing was conducted using SPSS software version 30.0. The primary instrument employed in this study was a critical thinking test in the form of an essay, developed based on Facione's theoretical framework.  The findings indicate that the integration of scaffolding into Problem-Based Learning (PBL) significantly enhances students’ critical thinking skills. Scaffolding optimizes the effectiveness of PBL, whereas PBL without scaffolding tends to be less effective in developing students’ potential evenly. These results suggest that mathematics teachers should implement scaffolding in a systematic and gradual manner to foster more reflective, structured, and higher-order thinking–oriented learning.